Molecular characterization of avian pathogenic Escherichia coli strains in Jiangxi Province, China, and development of polyvalent inactivated vaccines - Jia Tan; Ying-Xin Wang; Zhao-Feng Kang; Jiang-Nan Huang; Hai-Qin Li; Cheng-Cheng Wu; Na Li; Fan-Fan Zhang; Mei-Fang Tan (Poultry Science)
Avian pathogen Escherichia coli (APEC) poses a significant threat to poultry farming, causing colibacillosis in various hosts, including chickens, ducks, geese, and pigeons. This study aimed to investigate the molecular epidemiology of APEC in Jiangxi Province, China, to inform prevention and control strategies. Between 2020 and 2024, 186 APEC strains were isolated and identified, with 88.7 % from liver samples and 5.4 % from brain tissues. Whole-genome sequencing and analysis revealed that serotypes O145, O78, O8, and O111 comprised 32.9 %, 9.3 %, 7.9 %, and 4.3 % of the isolates, respectively. The dominant H serotypes included H21 (23.8 %), H9 (22.7 %), and H4 (18.2 %), with ST23 being the most prevalent sequence type at 24.2 %, followed by ST117 (10.1 %) and ST2505 (7.3 %). Virulence-associated genes in the strains O145, O78, O8, and O111 were further analyzed for quantity and pattern. Eight strains were selected for in vivo pathogenicity testing in ducks, four highly pathogenic strains were then identified, which were used to develop inactivated vaccines with the novel aqueous adjuvant MONTANIDE™ GEL P PR and the traditional adjuvant alumVax hydroxide. Compared with existing vaccines, those formulated in this study showed superior protection, with the MONTANIDE™ GEL P PR adjuvant achieving the highest protection rate (90.0 %, 36/40) and lower lesion scores. This research enhances the understanding of APEC epidemiology and offers promising strategies for effective vaccine development against prevalent APEC.